Interactive Animation Design of Hijaiyah Letters in Early Age Children at Al-Hidayah Kindergarten Bekasi - Dharmawati, Rika; Destiana, Henny (Politeknik Ganesha Medan, 2019)
Education about religious sciences, especially hijaiyah letters is very important as a provision to be understood by humans as the basis of their lives to face life in the future. The difficulties experienced are quite reasonable, because the Al-Qur'an uses Arabic. Learning with the Koran system is usually done in a relatively long time even sometimes for years. This is not effective and efficient in teaching and learning activities. So with the presence of a new learning media to utilize computer technology, it is expected to be developed into an interesting learning for kindergarten children. Therefore, the authors make interactive animated hijiayah letter recognition so that with interactive application of the introduction to hijaiyah letters for early childhood at Al-Hidayah Kindergarten Bekasi is very helpful in teaching and learning process to be more fun and effective so students are no longer bored in learning and attracted the interest of students to a better understand on how to read good and correct hijaiyah letters. As well as helping teachers to innovate in learning process because with this interactive animation application the instructors become easier to deliver material about the prayer movements to students.